2021
DOI: 10.4103/ijem.ijem_276_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Safety and Efficacy of Glimepiride-Metformin and Vildagliptin- Metformin Treatment in Newly Diagnosed Type 2 Diabetic Patients

Abstract: Objective: To compare the safety and efficacy of glimepiride and vildagliptin as add-on therapy to metformin in newly diagnosed patients with type 2 diabetes mellitus (T2DM). Methods: This 24-week, prospective, comparative, observational study was conducted among newly diagnosed patients with T2DM. The primary endpoint was a change in fasting plasma glucose (FPG), postpradinal glucose (PPG), and HbA1c from the baseline to week 24. The key secondary endpoints were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…In another similar study, patients treated with vildagliptin and metformin proved to be equally effective to glimepiride and metformin in control of blood glucose level 14 . A previous study revealed that metformin was not effective in controlling the levels of HbA1c, FBS and PPBS over glimepiride but effective in controlling total cholesterol (TC), low density lipoprotein (LDL) and triglycerides (TG) 15 .…”
Section: Discussionmentioning
confidence: 89%
“…In another similar study, patients treated with vildagliptin and metformin proved to be equally effective to glimepiride and metformin in control of blood glucose level 14 . A previous study revealed that metformin was not effective in controlling the levels of HbA1c, FBS and PPBS over glimepiride but effective in controlling total cholesterol (TC), low density lipoprotein (LDL) and triglycerides (TG) 15 .…”
Section: Discussionmentioning
confidence: 89%
“…Sedangkan pada kelompok kombinasi glimepiride 2mg-metformin 500mg sebanyak 8 sampel (20,00%) dengan rata-rata biaya pengobatan Rp 2.198.060,00. Hasil penelitian serupa yang meneliti tentang perbandingan keamanan dan kemanjuran pengobatan glimepiride-metformin dan vildagliptin-metformin pada pasien diabetes tipe 2 yang baru terdiagnosis menunjukan efektifitas yang sama dalam menurunkan kadar HbA1c dan parameter glukosa darah, namun menghasilkan profil efek samping yang lebih baik dengan risiko hipoglikemia yang lebih rendah [17].…”
Section: Keteranganunclassified